The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1093/alcalc/agu090
|View full text |Cite
|
Sign up to set email alerts
|

Brief Intervention in the Workplace for Heavy Drinkers: A Randomized Clinical Trial in Japan

Abstract: BI in the workplace is effective for increasing the number of alcohol-free days. However, the effectiveness on decreasing alcohol consumption was unclear, which could be explained by alcohol screening itself causing a reduction in drinking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 26 publications
1
36
0
Order By: Relevance
“…This finding suggests that occupational health staffs need to monitor the mental health of men who start regularly drinking 80 g or more of alcohol per week. This threshold is much lower than actual levels of alcohol consumption among candidates for brief interventions5, 6, 7 ) , which are considered effective to reduce alcohol consumption. Thus, it is necessary to focus not only on alcohol consumption but also on changes in drinking habits and onset.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…This finding suggests that occupational health staffs need to monitor the mental health of men who start regularly drinking 80 g or more of alcohol per week. This threshold is much lower than actual levels of alcohol consumption among candidates for brief interventions5, 6, 7 ) , which are considered effective to reduce alcohol consumption. Thus, it is necessary to focus not only on alcohol consumption but also on changes in drinking habits and onset.…”
Section: Discussionmentioning
confidence: 87%
“…It is therefore necessary to prevent poor mental health in the workplace. Poor mental health is associated with alcohol intake4 ) , and some studies have used methods such as brief interventions5, 6, 7 ) to induce heavy drinking workers to change their drinking patterns.…”
Section: Introductionmentioning
confidence: 99%
“…The authors confirmed the viability of alcohol consumption screening and the effect on the reduction of the consumption by workers, corroborating some international studies carried out in worker health services of some companies. 7,9,[16][17] The workers that had a high risk of alcohol consumption reduced their excessive consumption, although they did not consider themselves as people who drink too much. Some studies show that 9/12 the decrease is higher in the three first months after the BI and tends to diminish over time, which emphasizes the need for worker health teams to monitor the participants.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to stress the need to keep the follow-up and monitoring of the examined workers. [7][8][15][16][17][18][19][20] The present study emphasized the importance of carrying out screening procedures in worker health services asking health-related questions in periodic tests, as exemplified by the Worker Health Booklet in association with the AUDIT questionnaire. This strategy allows to obtain more reliable answers regarding alcohol consumption and higher adherence to the treatment, allowing to standardize team care.…”
Section: Discussionmentioning
confidence: 99%
“…The calendar style exerted a self-monitoring effect, as participants were able to grasp the relationship between changes in their behavior and alcohol consumption, such as "the relationship between weekend dinner parties and alcohol consumption" and "setting alcohol-free days and its effects", at a glance. While the introduction of a drinking diary was not shown to exert a significant effect in one study [43], Hara et al [44] described the effectiveness of moderate-drinking goals and a drinking diary. Nevertheless, with the finding that levels of achievement of behavioral goals were high in the HAPPY Plus, using a longer measurement period, it is conceivable that results could be reflected in improved physiological indicators and AUDIT scores.…”
Section: Effects Of the Happy Plus Vs The Happymentioning
confidence: 99%